Empirical Modelling of Consumer Price Index of Electricity and Percentage Inflation for Dhofar Governorate in Sultanate of Oman - K.J. Saravanaraj; L. Gerardo; S. Sivamani (PT FORMOSA CENDEKIA GLOBAL, 2022)
The aim of the present work is to develop a mathematical model relating the electricity consumer price index over the period from January 2013 to March 2022. The data was collected from the Data Portal of National Centre for Statistics and Information, Oman. The electricity consumer price index was constant at 100 from January 2013 to August 2012 and changed from September 2021 to January 2022 and then remained constant, Linear, quadratic, cubic, quartic, quintic, exponential, logarithmic and power models were used to fit the collected data. Based on R2, the quantic model fitted well with the collected data. The results showed the best goodness of fit between collected and model-predicted values.